Digital Solutions in a Time of Crisis : Uganda Economic Update, Fifteenth Edition, July 2020 - World Bank (World Bank, Washington, DC, 2020)
The COVID-19 (Coronavirus) pandemic in Uganda has emerged as the most significant adverse shock the global economy has experienced since the Second World War. It has taken a toll on human life and brought major disruption to countries across the globe. As a result, Uganda’s economy is expected to slow significantly in 2020 and early 2021, and the outlook on all fronts has deteriorated significantly. There are, however, areas of the economy that have shown resilience and are already adjusting to the current crisis as an opportunity to invent new ways of operating and doing business. Digital technologies offer a chance to unlock new pathways for rapid economic growth, innovation, job creation, and access to services for underserved populations. Digital technologies have the potential to boost productivity and create better jobs in the private sector, including for informal businesses. This report comes at a crucial time with Uganda in the grips of the COVID-19 (Coronavirus) pandemic. Digital solutions have already been significant in responding to the crisis and will be important as Uganda recovers and aims to build-back-better.